AWS Certified Cloud Practitioner (CLF-C01) - Daswani, Rajesh (Packt Publishing, 2019)
A comprehensive study guide for the AWS Certified Cloud Practitioner exam About This Video You'll understand the fundamentals of cloud computing and business/technical strategies to help you deploy highly available, fault-tolerant, scalable, and cost-effective IT solutions for your business. Build applications and solutions for your business and clients with fast turnaround times and gain a competitive edge This course will prepare you for the AWS Certified Cloud Practitioner Certification exam In Detail This AWS Certified Cloud Practitioner course is for anyone keen to learn and understand Amazon AWS Cloud's core offerings. It targets individuals who have no prior knowledge of Amazon AWS and wish to grow their career by effectively demonstrating an overall understanding of the AWS Cloud, its services, and how it can help deliver cost-effective IT solutions to meet business demands. After taking the AWS Certified Cloud Practitioner course, you will be able to demonstrate a detailed understanding of cloud concepts, AWS services, security and compliance, architectural concepts, cloud-pricing concepts, and support models. You will be able to confidently work on the AWS Cloud platform and start building cloud solutions. This course will prepare you for the AWS Certified Cloud Practitioner Certification exam.